2013
DOI: 10.1097/nen.0b013e31829e4963
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Cerebral Ischemia-Induced Neurogenesis

Abstract: Cerebral ischemia induces neurogenesis including proliferation and differentiation of neural progenitor cells and migration of newly generated neuroblasts. microRNAs (miRNAs) are small non-coding RNAs that decrease gene expression through mRNA destabilization and/or translational repression. Emerging data indicate that miRNAs have a role in mediating processes of proliferation and differentiation of adult neural progenitor cells. This article reviews recent findings on miRNA profile changes in neural progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 98 publications
1
58
0
Order By: Relevance
“…Exosomes are emerging as important intercellular players in mediating neurorestorative events after stroke and neural injury (139)(140)(141). Preliminary work demonstrates that either naturally occurring or engineered exosomes derived from stem/progenitor cells provide therapeutic benefits (139)(140)(141).…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are emerging as important intercellular players in mediating neurorestorative events after stroke and neural injury (139)(140)(141). Preliminary work demonstrates that either naturally occurring or engineered exosomes derived from stem/progenitor cells provide therapeutic benefits (139)(140)(141).…”
Section: Perspectivesmentioning
confidence: 99%
“…Preliminary work demonstrates that either naturally occurring or engineered exosomes derived from stem/progenitor cells provide therapeutic benefits (139)(140)(141). However, there are multiple unanswered questions and challenges in the development of exosome therapy including the following: (a) identification of the cellular signals by which the ischemic brain is able to affect the content and quantity of exosomes released by brain parenchymal cells and by remote organs, (b) understanding how exosomal cargo affects expression of endogenous genes and proteins in recipient cells of injured brain, (c) delineation of the specific cell types that are targeted by brain parenchymal cell-derived exosomes, and (d) knowledge of the effects of sex, age, and comorbidity on the cellular generation of exosomes and their cargo and the effect of sex, age and comorbidity in response to exosome treatment after stroke.…”
Section: Perspectivesmentioning
confidence: 99%
“…70,84 Also like the cells in the SGL, those NPCs that do survive migrate out of the SVZ into the striatum and neocortex and mature into functional neurons. 73,[85][86][87][88][89] In addition, it has been demonstrated that transient angiogenesis after stroke allows neuroblasts to migrate along these newly formed blood vessels aiding in their migration out of the SVZ.…”
Section: Effect Of Ischemia On Neurogenesismentioning
confidence: 99%
“…80 Stroke upregulates Shh expression in V/SVZ neural progenitor cells. 81 Inhibition of the Shh pathway reduces proliferation and differentiation of neural progenitor cells, whereas intraventricular infusion of exogenous Shh enhances stroke-induced neurogenesis. 81,82 The bone morphogenic protein (BMP) and Wnt pathways also regulate neurogenesis and oligodendrogenesis.…”
Section: Perinatal H/i Injury and Stroke-induced Oligodendrogenesismentioning
confidence: 99%
“…81 Inhibition of the Shh pathway reduces proliferation and differentiation of neural progenitor cells, whereas intraventricular infusion of exogenous Shh enhances stroke-induced neurogenesis. 81,82 The bone morphogenic protein (BMP) and Wnt pathways also regulate neurogenesis and oligodendrogenesis. Overexpression of BMP7 in ependymal cells inhibits neural progenitor cell proliferation and neuroblast production.…”
Section: Perinatal H/i Injury and Stroke-induced Oligodendrogenesismentioning
confidence: 99%